Design and Evaluation of a Web-Based Symptom Monitoring Tool for Heart Failure. Issue 5 (May 2017) - Wakefield, Bonnie J.; Alexander, Gregory; Dohrmann, Mary; Richardson, James
Abstract : Heart failure is a chronic condition where symptom recognition and between-visit communication with providers are critical. Patients are encouraged to track disease-specific data, such as weight and shortness of breath. Use of a Web-based tool that facilitates data display in graph form may help patients recognize exacerbations and more easily communicate out-of-range data to clinicians. The purposes of this study were to (1) design a Web-based tool to facilitate symptom monitoring and symptom recognition in patients with chronic heart failure and (2) conduct a usability evaluation of the Web site. Patient participants generally had a positive view of the Web site and indicated it would support recording their health status and communicating with their doctors. Clinician participants generally had a positive view of the Web site and indicated it would be a potentially useful adjunct to electronic health delivery systems. Participants expressed a need to incorporate decision support within the site and wanted to add other data, for example, blood pressure, and have the ability to adjust font size. A few expressed concerns about data privacy and security. Technologies require careful design and testing to ensure they are useful, usable, and safe for patients and do not add to the burden of busy providers.